Development ESP in English Language Learning for Work Readiness in Aviation and Shipping Vocational Schools - Serina, Serina; Nugraha, Hendra (English Language Education, Universitas Internasional Batam, 2025)
This study aims to investigate students’ English learning needs and the use of technology to support instruction in aviation and shipping vocational programs. Using a qualitative approach, data were collected through classroom observations and semi-structured interviews to explore students’ language challenges, learning preferences, and teachers’ instructional practices. The participants consisted of 16 twelfth-grade students and one English teacher from a vocational school in Batam. The findings reveal that students face significant difficulties in listening and grammar, which reduce their confidence in speaking, while English instruction remains general and not aligned with the specific demands of each department. Technology was available but used minimally and primarily for basic presentations rather than interactive learning. These results highlight the need to implement profession-oriented English learning supported by interactive digital tools to increase motivation, develop communication skills, and enhance students’ readiness for the aviation and maritime workplace. Overall, this study contributes by providing insights into learners’ specific needs and emphasizing the importance of integrating targeted ESP instruction with meaningful technology use in vocational contexts.